Vehicle End Connection Installment Relative Position Simulating Platform Based on ADAMS/rail Redevelope - 马鹏; 付茂海; 向阳; 王小中 (机车电传动)
In order to simulate the relative position of adjacent vehicle end connection installment under different line conditions, a software-platform based on ADAMS/rail was developed. All kinds of templates of carbody , bogie and connecting device were established, and muti-vehicle model was built by applying designated dialog box. With designated request, relative location of end vehicle was simulated.